Improvement and Variability of Adolescent Backstroke Swimming Performance by Age - Alshdokhi, Khaled; Petersen, Carl; Clarke, Jenny (Frontiers in Sports and Active Living, 2020)
To predict future performance, coaches rely on their previous experiences with a relatively small number of adolescent competitive swimmers to estimate the rate of improvement. The purpose of this study is to quantify the annual change in competition performance as backstroke swimmers mature. Data from 2006 to 2017 provided 9,956 swimming years of accumulated data which was used to estimate the rate of improvement of male and female backstroke swimmers as they aged from 8 to 18 years. Swimming performance improved rapidly between 8 and 13 years, and improvements diminished as swimmers approached their performance potential around 18 years old. These results provide accurate age-based progression data for adolescent backstroke swimmers, providing baseline performance prediction for coaches to predict future performance as swimmers mature, and providing a measure against which potential improvements from novel coaching and training methods can be objectively evaluated.